Brief research report: autistic traits modulate the rapid detection of punishment-associated neutral faces - Saito, Akie; Sato, Wataru; Yoshikawa, Sakiko (Frontiers in Psychology, 2023)
Speedy detection of faces with emotional value plays a fundamental role in social interactions. A few previous studies using a visual search paradigm have reported that individuals with high autistic traits (ATs), who are characterized by deficits in social interactions, demonstrated decreased detection performance for emotional facial expressions. However, whether ATs modulate the rapid detection of faces with emotional value remains inconclusive because emotional facial expressions involve salient visual features (i.e., a U-shaped mouth in a happy expression) that can facilitate visual attention. In order to disentangle the effects of visual factors from the rapid detection of emotional faces, we examined the rapid detection of neutral faces associated with emotional value among young adults with varying degrees of ATs in a visual search task. In the experiment, participants performed a learning task wherein neutral faces were paired with monetary reward, monetary punishment, or no monetary outcome, such that the neutral faces acquired positive, negative, or no emotional value, respectively. During the subsequent visual search task, previously learned neutral faces were presented as discrepant faces among newly presented neutral distractor faces, and the participants were asked to detect the discrepant faces. The results demonstrated a significant negative association between the degrees of ATs and an advantage in detecting punishment-associated neutral faces. This indicates the decreased detection of faces with negative value in individuals with higher ATs, which may contribute to their difficulty in making prompt responses in social situations.